2014
DOI: 10.1007/s00228-014-1762-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of second-generation antipsychotics on selected markers of one-carbon metabolism and metabolic syndrome components in first-episode schizophrenia patients

Abstract: PurposeAlterations in one-carbon metabolism (OCM) have been repeatedly reported in schizophrenia. However, there is a scarcity of studies addressing the effects of antipsychotics on selected OCM markers in schizophrenia and provided results are inconsistent.MethodsWe recruited 39 first-episode schizophrenia (FES) patients and determined serum profile of total homocysteine (tHcy), folate, vitamin B12, lipoproteins and glucose at baseline and after 12 weeks of treatment with second-generation antipsychotics (SGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
1
26
1
1
Order By: Relevance
“…The reason behind this is mentally ill condition itself and medications. There is a considerable literature on the metabolic adverse effects of antipsychotic agents and, in particular, second generation antipsychotics (SGAs) appear to induce more weight gain and metabolic abnormalities than first generation antipsychotics (FGAs) [8]. However, in this study metabolic syndrome is more prevalence among trifluoperazine (70%) drug group than risperidone (66.6%) and olanzapine (53.12%).…”
Section: Discussioncontrasting
confidence: 49%
“…The reason behind this is mentally ill condition itself and medications. There is a considerable literature on the metabolic adverse effects of antipsychotic agents and, in particular, second generation antipsychotics (SGAs) appear to induce more weight gain and metabolic abnormalities than first generation antipsychotics (FGAs) [8]. However, in this study metabolic syndrome is more prevalence among trifluoperazine (70%) drug group than risperidone (66.6%) and olanzapine (53.12%).…”
Section: Discussioncontrasting
confidence: 49%
“…It will also be necessary to have studies adequately powered to allow for further group separation by sex because research in 2014 showed this to be an important factor in determining changes in folate cycle metabolites following antipsychotic administration. 42 Despite these intriguing findings, we acknowledge that this was an exploratory study with several limitations. First, this was a retrospective investigation that used existing blood samples from a relatively small sample size, preventing us from drawing conclusions about AAP-induced changes on the metabolome.…”
Section: Discussionmentioning
confidence: 89%
“…In the future, it will be important to capture changes in the metabolome before and for an extended period of time after AAP initiation and medication switches. It will also be necessary to have studies adequately powered to allow for further group separation by sex because research in 2014 showed this to be an important factor in determining changes in folate cycle metabolites following antipsychotic administration …”
Section: Discussionmentioning
confidence: 99%
“…Èçìåíåíèÿ â óðîâíÿõ ãîìîöèñòåèíà áûëè àññîöèèðîâàíû ñ ïîëîì è îñíîâíûìè ìåòàáîëè÷åñêèìè ïàðàìåòðàìè (èíäåêñ ìàññû òåëà, ãëþêîçà, òðèãëèöåðèäû è äðóãèå ïîêàçàòåëè) ó áîëüíûõ øèçîôðåíèåé ñ ïåðâûì ýïèçîäîì, ïîëó÷àþùèõ ìîíîòåðàïèþ àòèïè÷íûìè íåéðîëåïòèêàìè (îëàíçàïèíîì èëè ðèñïèðèäîíîì) [50].…”
Section: аминокислоты как маркеры терапевтического ответа на антипсихunclassified